MIGRANT WORKERS AND COLLECTIVE BARGAINING IN THE EUROPEAN UNION: THE POSITIVE OBLIGATIONS OF STATES UNDER THE EUROPEAN SOCIAL CHARTER - Puiu, Tatiana (International Journal of Legal and Social Order, 2026)
This paper examines the positive obligations of States Parties to the European Social Charter (ESC) to secure migrant workers’ collective bargaining rights and analyses their interaction with European Union (EU) law. It sets out the Charter framework, notably Article 5 on the right to organise and Article 6 on collective bargaining, read together with Article 19§4(b) on equal treatment in trade union membership and in the enjoyment of the benefits of collective bargaining, and analyses its interpretation in the supervisory practice of the European Committee of Social Rights (ECSR). The paper addresses both formal legal conformity and effective implementation in practice, with particular attention to discriminatory effects and structural impediments that may undermine the practical and effective exercise of these rights. It then examines the interaction between ESC obligations and EU internal market freedoms, as illustrated by the Viking and Laval judgments, and considers whether subsequent EU instruments, including Directive (EU) 2022/2041 on adequate minimum wages, reinforce collective bargaining as a policy objective. It concludes that, notwithstanding areas of convergence, ESC standards retain autonomous normative force and require practical and effective protection of migrant workers’ collective bargaining rights.